Draft Annual Plan 1979-80 (In 4 Volumes) Haryana State Vol. I - Planning Commission (Planning Commission, 1979)
The State Government has already proposed the 1978-83 Five Year Plan in accordance with the nationally formulated policies, priorities and objectives, keeping in view the peculiar needs and commitments of the State. The Plan, size proposed for the five year period 1978-83 is Rs 1254.04 crores. It has been assumed therein that the Plan size for the first year of the quinquennium would be Rs 210 crores, as approved for the year 1978-79 and as taken to be the basis at the time of the formulation of the Five Year Plan. The aforesaid outlay of Rs 210 crores was inclusive of an outlay of Rs 19 crores for the construction of the Sutlej Yamuna Link in the State of Punjab.
Planning Department, Government of Haryana